Hydroxymethylfurfural oxidation over unsupported Pd-Au alloy catalysts prepared by pulsed laser ablation: Synergistic and compositional effects - Timofeev, Konstantin L.; Kharlamova, Tamara S.; Ezhov, Dmitry M.; Salaev, Mikhail A.; Svetlichnyi, Valerii A.; Vodyankina, Olga V. (Applied catalysis A: General)
Bimetallic nanoparticles are of high interest for electronics, photonics, biomedicine, and heterogeneous catalysis. To reveal the effects of structure and composition of bimetallic nanoparticles on catalytic properties, unsupported particles with clean surfaces and well-defined characteristics should be considered. Herein, colloidal Au, Pd, and Au-Pd catalysts prepared by pulsed laser ablation in liquid are studied in 5-hydroxymethylfurfural (HMF) oxidation. The catalysts are characterized by ELS, UV–vis spectroscopy, XRD, TEM, and SAED methods. The results show the formation of Au1−yPdy alloy particles that remain stable in pure water without the presence of any surfactant and feature higher performance towards formylfuran carboxylic and furandicarboxylic acids as compared with monometallic samples. The results indicate the combined benefits of Pd1−yAuy alloys in aerobic catalytic HMF oxidation due to a synergistic effect comprising the formation of Au-Pd interface in alloy nanoparticles, where the metals activate different moieties of HMF molecule.